Efektifitas pemberian tablet fe dan madu terhadap kadar hemoglobin ibu hamil - Efia, Nur; Mariza, Ana; Evrianasari, Nita; Astriana, Astriana (JOURNAL OF Community Health Issues, 2023)
Anemia is a health problem in all over the world especially developing country which is estimated around 30% of world’s citizen suffer from anemia/ the number of anemia on pregnancy in Indonesia shows the high number which is 3.8% on trimester I, 13.6% on trimester II and 24.8% on trimester III. At Hajimena Health Centre of Natar sub-district South Lampung Regency has not handled anemia on pregnant woman yet by giving FE and honey. The researcher wants to know is there any affectivity of giving FE tablet and honey towards pregnant woman’s hemoglobin at the working area of Hajimena Health Centre of Natar sub-district South Lampung Regency. Quantitative research type with quasy experiment research design and two group pretest-posttest. The research population of anemia on pregnant woman as many as 79 people with the sample as many as 32 people, the sampling technique was Purposive Sampling. The data analysis was t-test univariate and bivariate. The influence of Fe tablet and honey giving towards pregnant woman’s haemoglobin at the working area of Hajimena Health Centre of Natar sub-district South Lampung Regency year of 2019 (t-test > t count 14.067, p-value 0.000 < 0.05). There were the difference of hemoglobin level on experiment group and control group where it was obtained t-test > tcount 8.292 > 1.725 p-value = 1.0004 (<α 0.05) which means there was the hemoglobin level difference between experiment group and control group, with mean difference as much as 0.8. Pregnant woman should improve consuming the food contains vitamin C, B12, folic acid and protein to improve FE absorption in the body and also to prevent consuming food source FE along with the food which can inhibit FE absorption such as tea, coffee and milk. Keywords : Hemoglobin level, pregnant woman, FE+Honey Anemia merupakan salah satu masalah kesehatan di seluruh dunia, banyak terjadi terutama pada ibu hamil. Madu merupakan panganan mengandung besi ( Fe ), Vitamin C, Vitamin B. Kompleks dan Asam Folat yang dapat membantu meningkatkan pembentukan sel darah merah dan mencegah anemia. Penelitian ini untuk mengetahui apakah ada efektifitas pemberian tablet Fe dan madu terhadap kadar hemoglobin ibu hamil di wilayah kerja Puskesmas Hajimena Kecamatan Natar Lampung Selatan tahun 2019. Jenis penelitian kuantitatif dengan rancangan penelitian quasi eksperimen atau eksperimen semu dengan two group pretest-postest. Populasi penelitian ibu hamil sampel sebanyak 32 orang, teknik sampling Purposive Sampling. Analisa data univariat dan bivariat uji t (t-test). Dari hasil penelitian yang dilakukan penulis didapat bahwa distribusi frekuensi kadar Hemoglobin ibu hamil sebelum pemberian Fe dan madu adalah 9,975 dengan standar deviasi 0,4187 dan distribusi frekuensi kadar Hemoglobin ibu hamil setelah diberikan FE dan madu adalah 11,213 dengan standar deviasi 0,3964. Ada pengaruh Pemberian Tablet Fe Dan Madu Terhadap Kadar Hemoglobin Ibu Hamil Diwilayah Kerja Puskesmas Hajimena Kecamatan Natar Kabupaten Lampung Selatan (t-test > t hitung 14,067, p–value 0,000 < 0,05). Terdapat perbedaan kadar hemoglobin pada kelompok eksperimen dan kelompok kontrol dimana didapatkan t- test > t hitung 8,292 > 1.725 p-value = 0,004 (< α 0,05) yang berarti ada perbedaan kadar haemoglobin antara kelompok eksperimen dan kelompok kontrol, dengan perbedaan nilai mean sebesar 0.8 point. Kata kunci: Kadar haemoglobin , ibu hamil, FE+Madu